Methodology of Literary Criticism Based on the Theory of Feminism - Bilal Ahmad Fazli (RIRAI Publisher, 2023)
Feminism is an organized movement to defend women's rights, whose roots go back to the Periods of European Enlightenment (Renaissance). Throughout its long history, this movement wanted to overthrow the patriarchal system and eliminate the rule of gender discrimination. Feminism officially began its activity at the end of the 18th century and has gone through a period full of ups and downs since then. The three important waves of this movement are considered to be one of its most important activities, whose basic goals are